Ganglion cell layer changes following the idiopathic macular hole surgery using inverted limiting membrane flap technique - Mehmet Önen; Muzaffer Şahin; Gökhan Çelik (BMC Ophthalmology)
Abstract Purpose The purpose of this study is to compare the ganglion cell layer changes following temporal inverted internal limiting membrane flap (i-ILMF) surgery for idiopathic macular hole (IMH). Methods This retrospective study included 50 eyes that underwent vitrectomy with a 2.5-disc-diameter temporal inverted internal limiting membrane flap (i-ILMF) technique. Demographic, functional, and anatomical data were collected before and after the surgery. The best corrected visual acuity (BCVA) and optical coherence tomography (OCT) findings such as ganglion cell layer -inner plexiform layer (GCL-IPL) thickness and hole related parameters/indexes were compared in the preoperative period and 6th month after surgery. Results The average age of the patients was 68.8 ± 10.31 years, and the average duration of visual loss was 10.95 ± 6.54 months. The average GCL-IPL thickness increased significantly from 57.98 ± 21.43 μm to 68.74 ± 13.62 μm at 6 months after surgery (p < 0.001). The nasal GCL-IPL thickness was significantly increased from 56.94 ± 24.18 μm to 73.10 ± 15.39 μm after 6 months after surgery (p < 0.001). Conclusion The temporal i-ILMF technique not only leads to high anatomical success and visual improvement but also results in a significant increase in GCL-IPL thickness postoperatively, suggesting a unique structural response to this method.